2015
DOI: 10.1111/dme.12966
|View full text |Cite
|
Sign up to set email alerts
|

Smoking affects the oral glucose tolerance test profile and the relationship between glucose and HbA1c in gestational diabetes mellitus

Abstract: In women with gestational diabetes mellitus who smoke at the beginning of pregnancy, the shape of the OGTT is consistent with accelerated glucose absorption, and HbA1c is higher than expected for glycaemic values.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 14 publications
1
7
0
1
Order By: Relevance
“…A recent meta‐analysis also reported 2‐hour postprandial concentrations to be lower in smokers compared with non‐smokers 24 . Likewise, also in pregnant women with GDM, 1‐hour postprandial concentrations have been shown to be higher and 2‐hour postprandial concentrations lower in women who smoked at the beginning of their pregnancy compared with non‐smokers 25 . None of these previous studies have reported any difference in fasting glucose concentrations.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…A recent meta‐analysis also reported 2‐hour postprandial concentrations to be lower in smokers compared with non‐smokers 24 . Likewise, also in pregnant women with GDM, 1‐hour postprandial concentrations have been shown to be higher and 2‐hour postprandial concentrations lower in women who smoked at the beginning of their pregnancy compared with non‐smokers 25 . None of these previous studies have reported any difference in fasting glucose concentrations.…”
Section: Discussionmentioning
confidence: 91%
“…To the best of our knowledge, few studies have evaluated the relation between smoking and glucose concentrations after an OGTT during pregnancy. 7,25 Compared with non-smokers, we discovered that primiparous women who continued smoking after the first trimester, had higher fasting glucose concentrations and higher 1-hour glucose concentrations. Women who stopped smoking after the first trimester, also had higher fasting glucose concentrations but not higher As a well-accepted phenomenon, 14 we also found offspring birthweight to be lowest in women who continued smoking after the first trimester compared with non-smokers.…”
Section: F I G U R Ementioning
confidence: 88%
“…Specifically, maternal smoking is associated with an increased risk of adverse obstetric effects 14 and placental vascular resistance 2 , miscarriage 14 , preterm birth 14 , abruption placenta 14 , placental previa 14 , preterm rupture of the membranes 14 , ectopic pregnancy 14 , stillbirth 14 , gestation diabetes mellitus 17 and fetal effects 14 , low birth weight 14 , small-for-gestational-age 14 , and Intra-Uterine Growth Retardation (IUGR) 14 . There is increased risk also of birth defects 2 including: limb reduction defects 14,17,18 , clubfoot 14,18 , cleft lip or palate 14,18 , anophthalmia 14,18 , microphthalmia 14,18 , esotropia 18 , exotropia 18 , optic nerve hypoplasia 18 , heart defects 14,18 , craniosynostosis 14,18 , gastroschisis 18 , anal atresia 14,18 , hernia 14,18 , and cryptorchidism 14,15,18 .…”
Section: Resultsmentioning
confidence: 99%
“…There is also evidence in terms of the adverse effects of maternal tobacco use extending to newborns and children. Namely, there is a significantly increased risk of sudden infant death syndrome 2,14 , obesity 2,14 , type 2 diabetes 2,14,17 , earlier menarche for girls 2 , and reduction in male reproduction ability 19 , respiratory effects (upper respiratory tract infections, bronchitis and other lower respiratory tract infections, pulmonary hypertension, compromised lung function, increased rate of lower respiratory tract infections, impaired lung function, wheezing and asthma 2,14 , cardiovascular effects (hypertension) 2,14 , neurologic effects (developmental abnormalities in the brain, decreased brain measurements, impairments in normal brain activity) 2 , neurodevelopmental and behavioral effects 2,14 (abnormal behavioral and neurodevelopmental outcomes) 2 , global intelligence/ academic performance 2 , Attention Deficit/ Hyperactivity Disorder (ADHD) 2,20 , externalizing behaviors 2,20 , antisocial behavior, nicotine dependence 14 and future substance abuse 2 , significant increase risk for early psychiatric disorders 21 in early adulthood, and necrotizing enterocolitis (NEC) 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Food intake would affect glucose tolerance [34]. Women who smoked had higher 1-h blood glucose (1hBG) than non-smokers, which also affected OGTT [35]. Coffee [36] and tea [37] could improve glucose tolerance and impair the test too.…”
Section: Methodsmentioning
confidence: 99%